MEASURING RETURNSS TO SCALE, DISTRIBUTION EFFICIENCY AND ESTIMATING WHEAT PRODUCTION FUNCTION IN DHI QAR PROVINCE - & et al., Barbaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this research was to estimate the production function to measure returns to scale and distribution efficiency of resources used in the production of wheat. Cross sectional data used of a random sample of 130 farmers in Dhi Qar Province. The results of the quantitative analysis of estimating production function showed that the double logarithmic form was the best estimated model based on economic and statistical indicators. However, that form suffered from heteroscedasticity and autocorrelation, so the robust regression technique was chosen. Value of returns to scale was 0.89 and this indicates decreasing returns to scale. This means that production function is in the second stage of the function. The results of the distributional efficiency study showed that the resources used in the production of the crop were not optimized as they amounted to 1.28 for the human labor resource and 20.6 for the capital. There was a shortage in the use of labor resource and capital for the optimal use that achieves economic efficiency and this caused low efficiency of crop production. Therefore, the research recommends the need to increase the amount of human labor in the wheat crop farms in Dhi Qar province, which would move the production function curve to a higher level in order to achieve the economic efficiency of the crop cultivation in the province on the one hand and return the farmers to production in the rational stage. Also, it is important to have the proper allocation of resources available by farmers, which has the effect of increasing the economic efficiency of those resources, which will in turn reflects on the efficiency of crop production.